2001
DOI: 10.1074/jbc.m007690200
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Regulator of a Pristinamycin Resistance Gene in Streptomyces coelicolor

Abstract: Pip is a pristinamycin-induced transcriptional regulator protein detected in many Streptomyces species by its ability to specifically bind sequence motifs within the promoter of a Streptomyces pristinaespiralis multidrug resistance gene (ptr). To investigate the possible role of Pip in regulating multidrug resistance, it was purified from a genetically characterized species, Streptomyces coelicolor, utilizing an affinity matrix of the ptr promoter conjugated to magnetic beads. Reverse genetics identified the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…Uncharacterized regulators designated Pip proteins have been proposed to be involved in the regulation of drug transport genes in a range of Streptomyces species (187,188). Isolation of the Pip protein from the genetically well-defined Streptomyces coelicolor indicated that it was a TetR family repressor that regulates the expression of the MFS antiporter Ptr, which confers resistance to the antibiotic pristinamycin I (34).…”
Section: Drug Transporter Expression In Other Pathogens and Antibiotimentioning
confidence: 99%
“…Uncharacterized regulators designated Pip proteins have been proposed to be involved in the regulation of drug transport genes in a range of Streptomyces species (187,188). Isolation of the Pip protein from the genetically well-defined Streptomyces coelicolor indicated that it was a TetR family repressor that regulates the expression of the MFS antiporter Ptr, which confers resistance to the antibiotic pristinamycin I (34).…”
Section: Drug Transporter Expression In Other Pathogens and Antibiotimentioning
confidence: 99%
“…When tetracycline enters the cytoplasm, it binds to TetR, inducing a conformational change that dissociates TetR from the tetA operator, allowing the production of TetA and the active efflux of tetracycline (18,19). This general regulatory mechanism has also been described previously for several members of the TetR family (6,9,12,31,39,47,51). Given that cholate, deoxycholate, and chenodeoxycholate induce breAB and breR expression, we hypothesized that these bile salts may interact with BreR.…”
mentioning
confidence: 99%
“…Antibiotic biosynthetic genes are found in clusters that typically include the corresponding resistance genes to provide selfprotection (10). However, as in other bacteria, genes scattered throughout the genome that may have alternative physiological roles can also confer antibiotic resistance (11). Intuitively, the protective activity of these resistance genes should be a prerequisite for the evolution of antibiotic biosynthetic pathways.…”
mentioning
confidence: 99%